Metaphor as a mechanism of global climate change governance: a study of international policies, 1992–2012 - Shaw, Chris; Nerlich, Brigitte (Elsevier, 2015)
This paper explores the emergence of a global climate change mitigation regime through an analysis of the language employed in international science-policy reports. We assume that a global climate regime can only operate effectively on the basis of a shared understanding of climate change which is itself based on a shared language of governance. We therefore carried out an in-depth thematic and metaphor analysis of 63 policy documents published between 1992 and 2012. Results show that global climate science-policy discourses universalise the myriad impacts of a changing climate into a single dichotomous impacted/not-impacted scenario and aim to govern this world according to economic principles of cost–benefit analysis. These discourses use metaphors that draw on narrative structures prevalent in the wider culture to produce and legitimate a reductionist representation of climate change. This representation undermines public understanding of and engagement with climate change by marginalising subordinate policy framings which do not align with the prevailing dichotomous framing. The types of documents we analyse in this paper represent important sources for journalists reporting on climate change. We therefore suggest that any attempt to improve public communication of climate change should include revisions to these organisational discourses.